WOLF (Wolverhampton Online Learning Framework) - O’Donoghue, John; Fleetham, Liz; Dalziel, Colin; Molyneux, Steve (Proceedings of the International Conference on Networked Learning, 2000)
The rationale for the creation of an online learning infrastructure is clearly multi-faceted. Infrastructure suggests connections, detail and possibly a fixed topology, but is this reasonable within the context of teaching and learning? The infrastructure. within Wolverhampton is complex. It has a large estate with multi campus cultures and traditions. The delivery mechanisms are based on a modular approach, often with multiple iterations, and there is a high percentage of mature and part-time students. Consistency of approach to delivery is paramount, but very few flexible learning environments existed. It was from this premise that our bespoke solution, WOLF, was developed - answering a need to embark upon a radical appraisal of all learning and teaching aspects.